“Uma outra porta”: a contribuição da advocacia pública municipal na implantação e implementação de políticas públicas - Santos, Márcia de Barros Lima (2021)
This paper analyzes County Public Advocacy as a sector that contributes to the implementation of public policies, an obligation of the State to do. The text highlights the necessary recognition of county public advocacy and the intersectoriality with public agents who carry out public policies and social rights. At first, it briefly analyzes the public policy on social assistance that gave rise to the study, normative evolution and the offer of social protection in the country, which meant socio-political commitment over the 35 years it was created, but which currently undergoes the lack of public funding that deprives it of the possibility of achieving its goals. The social assistance policy was analyzed to demonstrate its importance as a social right and the need to defend its continuity. The text provides information on social rights and public policies, highlighting the historical process that took place in the Western world and in Brazil and how Constitutionalism and the Social States gave rise to fundamental rights based on the principle of human dignity. It is, therefore, about knowing and extolling the Welfare State and social rights in Democratic States of Law, however without forgetting to analyze the crises of the socio-economic system and the losses for the working class. From the State's de-responsibility for the obligation to do it and from the market dispute for the Public Fund, the unfeasibility of the State primacy, universality and gratuitousness of the offer of public shares is evidenced. Talking about the public administration, the place of the public agent in the implementation of policies and the challenges for the consolidation of public policies proved to be necessary because the critical awareness of the public agent must be fostered and leading workers to greater participation in intersectoral debates in favor of defense of rights surpassing values historically instilled in public institutions, which leads us to a brief analysis of the successive administrative reforms that harm the public agent and the provision of services. The articulation of public agents in intersectoriality with the County Public Advocacy highlights the importance of defending sectorial public causes, recognizing the role of the sector and its importance in public administration in the defense of the Federal Constitution, legality and the obligation to make the State the which means the defense of the citizen